Corrosion mitigation of mild steel over thicknesses of graphene oxide/polyaniline nanocomposite coatings - Rihashni, Thivagaran; Mohd Radzi, Aridi; Nurjannah, Salim; Siti Maznah, Kabeb; Nurul Huda, Abu Bakar (John Wiley & Sons, Inc., 2025)
Epoxy is frequently employed as a protective coating to inhibit corrosion. Over the years, researchers have focused on improving the barrier properties of epoxy coatings because prolonged exposure to harsh environments may induce corrosive ion permeation. In this regard, polyaniline functionalized graphene oxide (GO/PANI) nanocomposite is introduced into the epoxy matrix to enhance the barrier performance. GO is first sonicated at 5 h to yield smaller graphene sheet sizes and to ensure uniform suspension. The research reveals that thicker coating with five layers of the nanocomposites (GO/PANI-5) successfully protects mild steel substrates at a corrosion rate (CR) of 0.0037 mm y−1 compared to pure epoxy coating at an equivalent thickness (≈0.016 mm year−1). Detailed investigation of electrochemical impedance spectroscopy (EIS) shows that the GO/PANI-5 coating exhibits higher impedance with four to five orders of magnitude than the pure epoxy and bare mild steel substrate. The significant findings denote that a thicker layer with a smaller GO sheet allows for more barrier characteristics due to stronger adhesion and slower ion diffusion rate. To conclude, incorporating GO/PANI nanocomposites will add more protective values to pure epoxy and provide multifaceted applications regardless of thickness.